Problem of patient safety in cardiас surgery and strategy to reduce risk of postoperative complications - V. V. Lazorishinets; A. A. Krikunov; A. B. Koltunova; R. V. Buryak; S. V. Shevchuk (Ukrainian Journal of Cardiovascular Surgery, 2017)
The effectiveness of cardiac surgical care is based on a clear strategy to identify preoperative risk factors and development of protocols for the prevention of various intraoperative and postoperative complications.Objective: To develop strategy to reduce risk of intra / postoperative complications and lethal outcomes in cardiac surgical patients.Materials and methods. From 01.01.1993 to 31.12.2016 surgical treatment of 100 212 patients was performed at SE “Amosov National Institute of Cardiovascular Surgery NAMS of Ukraine”. The basis of the strategy to reduce postoperative complications and hospital mortality is stratification of preoperative risk factors and development of protocols for perioperative management of cardiac surgical patients.Results and discussion. The number of cardiac surgical interventions in the treatment of congenital heart diseases showed decrease in hospital mortality from 3.8% (2014) to 1.8% (2016), while the expected mortality on the Aristotel scale varied from 5.3 to 6.5. The rate of surgical interventions for infective endocarditis increased from 63 (1993) to 236 (2016) patients respectively. Hospital mortality decreased from 14.2% (1994) to 2.1% (2016) cases respectively. In the EuroSCORE system, patients with complicated course of infective endocarditis had a predicted mortality rate of 18.9%. Due to the developed protocols of perioperative management, hospital mortality in this pathology decreased to 2.1% (2016). Analysis of hospital mortality levels in surgical treatment of coronary heart disease revealed reduction in lethal cases: from 2% (2001) to 0.4% (2016), respectively.Conclusions. The developed strategy of perioperative support in surgical treatment of high risk patients contributed to a radical reduction in postoperative complications and hospital mortality.